Butea monosperma: An Ornamental Plant to Precious Herb - A. V, Shrirao (International Journal of Pharmaceutical & Biological Archive, 2017)
Since ancient times plants are used for their medicinal and cosmetic properties. India has well-recordedand well practiced knowledge of traditional herbal medicine. Butea monosperma popularly known asFlame of the Forest, Dhak, Palash or ‘Bastard teak’ which has immense potential and appears to have abroad spectrum of activity on several ailments. Previous phytochemical examination of this plantindicated the presence of various constituents some of these are Cajanin and isoformononetin; Stigmasterol; Butin; two known flavonoids, isobutrin (3, 4, 2', 4'-tetrahydroxychalcone-3, 4'-diglucoside), andthe less active butrin (7, 3', 4'-trihydroxyflavanone-7, 3'-diglucoside); free sugars and free amino acidsand (-)-3-hydroxy-9-methoxypterocarpan[(-)-medicarpin which were isolated from stem-bark extract;bark; seeds; flower; the petroleum ether extract of flowers and petroleum and ethyl acetate extract of stembark. Many reported pharmacological properties include anthelmintic, anticonceptive, anticonvulsive,antidiabetic, antidiarrhoeal, antiestrogenic and antifertility, antiinflammatory, antimicrobial, antifungal,antibacterial, antistress, chemopreventive, haemaggultinating, hepatoprotective, radical scavenging,Thyroid inhibitory, antiperoxidative and hypoglycemic effects and wound healing activities. Other thenthis Ayurvedic herbal medicine which was prepared from Piper longum (Pippali) and Butea monosperma(Palash) has significant activity against Giardiasis.